Psychometric Properties of the Turkish Version of Prolapse and Incontinence Knowledge Questionnaire - Korkut, Arife; Citak Karakaya, Ilkim; Yenisehir, Semiha; Karakaya, Mehmet Gurhan (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: This study aimed to translate and culturally adapt the prolapse and incontinence knowledge questionnaire into Turkish, and to investigate the psychometric properties of the Turkish version prolapse and incontinence knowledge questionnaire. STUDY DESIGN: Psychometric properties of the Turkish version prolapse and incontinence knowledge questionnaire, which was developed according to standard scientific translation procedures, were analyzed on 206 volunteer women (31.79±8.79-year-old), after being tested for its comprehensibility and content validity. The participants were questioned about their physical and socio-demographic characteristics, obstetrical-gynecological histories and menstrual states, current medical complaints, and reasons for applying to the clinics. In addition to Turkish version prolapse and incontinence knowledge questionnaire, they completed the Turkish incontinence quiz, global pelvic floor bother questionnaire, pelvic floor distress inventory-20 and pelvic floor impact questionnaire. Retests were performed on 27 participants, after one week. Internal consistency, test-retest reliability, and construct validity of the Turkish version prolapse and incontinence knowledge questionnaire were investigated. RESULTS: Internal consistencies of the Turkish version prolapse and incontinence knowledge questionnaire subscales (Turkish version prolapse and incontinence knowledge questionnaire-UI and Turkish version prolapse and incontinence knowledge questionnaire-pelvic organ prolapse) were high (Cronbach α=0.754 for both); item-total correlations were 0.127-0.576 and 0.217-0.509, respectively. Also, test-retest reliabilities of the subscales and the overall scale were high (Intraclass correlation coefﬁcient =0.949, 0.911 and 0.878, respectively). Turkish version prolapse and Incontinence knowledge questionnaire scores were highly correlated with incontinence quiz scores and weakly correlated with pelvic floor distress inventory-20 and pelvic floor impact questionnaire-7 scores (p<0.05). CONCLUSION: It was concluded that Turkish version prolapse and incontinence knowledge questionnaire is a reliable and valid tool to measure Turkish women’s knowledge and awareness about urinary incontinence and pelvic organ prolapse.